2015
DOI: 10.5539/gjhs.v8n1p255
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Risk Factors in Patients With Myocardial Infarction

Abstract: Background:Coronary artery diseases (CAD) are one of the important health problems in the world, although considerable progresses have been made to decrease the mortality, they are still the first cause of death in many countries. Hence, the necessity of examining effective factors and risk factors on CAD can be one of the most important health priorities in many countries like Iran.Objective:This study was performed to assess the risk factors in patients with myocardial infarction (MI) in Zahedan.Materials an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 29 publications
2
25
0
3
Order By: Relevance
“…Scientific research conducted over the years into predictive factors for AMI have shown that age and gender are two of the main predictors [7][8][9][10]. In their study into demographic risk factors related to the occurrence of myocardial infarction, Duan et al [7] showed that myocardial infarction is more prevalent among men than women, and that this risk increases considerably above the age of 50.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Scientific research conducted over the years into predictive factors for AMI have shown that age and gender are two of the main predictors [7][8][9][10]. In their study into demographic risk factors related to the occurrence of myocardial infarction, Duan et al [7] showed that myocardial infarction is more prevalent among men than women, and that this risk increases considerably above the age of 50.…”
Section: Discussionmentioning
confidence: 99%
“…The odds ratios (OR) were calculated for the following, which are also considered to be AMI predictors: GCS 9-12 points OR=3.442 (CI 95%) and swelling OR=3.572 (CI 95%). Kiani et al [10] analyzed risk factors for patients with myocardial infarction treated in hospital. They demonstrated a statistically significant dependency for sinus rhythm, atrial fibrillation, ventricular tachycardia atrioventricular blocks.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the prevalence of MI has been increased in both developed and developing countries [14,15]. Research evidences indicate that such risk factors as age, sex, and family history cannot be modulated, but some of the risk factors such as ambient air pollution and unhealthy life style are to a great extent preventable [16][17][18]. Considering the fact that the age for onset of the first MI has been decreasing and that MI is multifactorial in nature, its fundamental function remains unknown [19].…”
Section: Introductionmentioning
confidence: 99%
“…The demographic characteristics examined in the study population included age group (15e18 years and 19e22 years), gender (male or female), and race (white, Black, Hispanic, Asian, Native American, and other). Based on the current literature [22,23], we identified suspected risk factors for AMI and comorbid substance use as well as psychiatric disorders using ICD-9-CM diagnosis codes and CCS codes, respectively.…”
Section: Variablesmentioning
confidence: 99%